Coaching Clinic Table Tennis for Students to Improve Basic Technical Skills - Yully Wahyu Sulistyo; Mohammad Zaim Zen; Masruchan; Ulil Amallia Dwi Tantri (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2026)
This community service activity was carried out based on the problem of students' understanding of basic table tennis skills, so there was a need for an activity that could support the understanding of basic table tennis skills, using an educational and participatory approach that combined lectures and practice. The participants of this community service activity were 65 physical education students who were taking a table tennis course. The results of the community service activity showed that the initial data was in the poor category (52.30%). After learning the initial data results, the students practised the material and the final results were in the good category (36.92%). From this data, it can be seen and understood that this community service activity had a positive impact on basic table tennis skills.